Effect of microstructure on the electrochemical dissolution behaviour of Hastelloy® X superalloy processed by selective laser melting and heat treatments. (August 2021) - Yin, Yingyue; Zhang, Jianhua; Yang, Shengzhao; Liu, Tong; Han, Quanquan; Zhang, Zhenhua; Yang, Huanqing
Graphical abstract: Highlights: Electrochemical corrosion resistance of selective laser melting fabricated Hastelloy® X under as-received, solubilisation, aging and solubilisation + aging treatment was evaluated. Dissolution behaviour enhanced through decreasing compact oxides on passive film. A new indicator I to describe the dissolution rate of passive film was proposed based on the components of product. The enhanced mechanism of microstructure-dependent dissolution behavior was revealed by the galvanic cell corrosion effect and passive evolution. Abstract: As a proven and highly efficient processing technique, electrochemical machining (ECM) is used for machining difficult-to-cut Ni-based superalloys (such as Hastelloy® X [HX] fabricated via selective laser melting [SLM]) with complex shapes. However, the metallic surface is susceptible to passive film formation to reduce the dissolution rate of HX under low current density conditions during the ECM process. This study focused on optimising microstructures for SLM-fabricated HX via heat treatment to enhance its electrochemical dissolution behaviour. The rates of electrochemical dissolution with different heat treatments increased in the following order: as-received < solution treatment (ST) < ageing treatment (AT) < solution and ageing treatment (ST + AT) in a 10 wt% NaNO3 solution at 35 °C. These results are attributed to 1) a large number of two representative precipitates (Fe2 Mo and M23 C6 ) in the grain or on the grain boundary (GB), 2) the decreased low-angle GB density (1.71%) and 3) few compact products on the surface of the samples with ST + AT. The parameter I, which is related to surface product composition, was quantitatively characterised based on the electrochemical dissolution rate of the samples. The enhanced mechanism of electrochemical dissolution is proposed to offer new insights into Ni-based superalloys in ECM applications.